Association Between Dietary Fiber Intake and Non-alcoholic Fatty Liver Disease in Adults - Zhao, Huimin; Yang, Aihua; Mao, Lina; Quan, Yaning; Cui, Jiajia; Sun, Yongye (Frontiers in Nutrition, 2020)
Background: Evidence on the association of nonalcoholic fatty liver disease (NAFLD), a public health concern, with dietary fiber intake is limited. Objective: To investigate the relationship between dietary fiber intake from different sources and NAFLD risk in US adults. Methods: Data were collected from the 2007–2014 National Health and Nutrition Examination Survey. NAFLD was defined as a United States Fatty Liver Index ≥30, and dietary fiber intake was assessed through two 24-hour dietary recall interviews. Logistic regression and restricted cubic spline models were used to explore the relationship of dietary intakes of total, cereal, fruit, and vegetable fiber with NAFLD risk. Results: A total of 6,613 participants, aged more than 20 years, were included in this study. After adjusting for multiple confounding factors, the odds ratios and 95% confidence intervals of NAFLD for the highest quartile versus lowest quartile intakes of total, cereal, fruit, and vegetable fiber were 0.12 (0.08–0.16), 0.25 (0.19–0.33), 0.41 (0.33–0.52), and 0.42 (0.32–0.56), respectively. In stratified analyses by sex and age, statistically significant negative associations of dietary intakes of total, cereal, fruit, and vegetable fiber with NAFLD risk were observed in all participants. Dose-response analysis indicated a nonlinear correlation between NAFLD risk and dietary intake of total fiber, whereas the relationship was linear for cereal, fruit, and vegetable fiber intakes. Conclusion: Total, cereal, fruit, and vegetable fiber intakes exhibit negative correlations with NAFLD risk in the general adult population in the United States.